Characterization of Novel Injectable Lifting Agents Used in Colonic Polyp Removal: An Emerging Amyloid Mimic. (June 2020) - Pezhouh, Maryam K.; Burgart, Lawrence J.; Chiu, Kenrry; Cohen, David A.; Hutchings, Danielle A.; Sanderson, Schuyler O.; Shirazi, Maryam; Stanich, Peter P.; VandenBussche, Christopher J.; Voltaggio, Lysandra; Willhoit, Ellen D.; Xue, Yue; et al.
Abstract : Colon polypectomy can require an injection of a submucosal lifting agent to fully visualize and completely remove the polyp. To the best of our knowledge, this is the largest morphologic series on the novel lifting agents Eleview and Orise. The study consisted of 1 polypectomy and 8 colon resections from 9 patients: 6 women, 3 men (mean age=64 y); Orise=6, Eleview=3; the median time interval between injection and resection=16 weeks. Pathologic diagnoses of the polyps included tubular adenoma (n=4), tubulovillous adenoma (n=4), and sessile serrated adenoma/polyp (n=1). We report that a histologically processed Orise aliquot from the manufacturer showed similar histology to that seen in the specimens from patients with confirmed Orise injection. The morphology of the agents in the patient specimens changed with time status postinjection: immediate resection of the lifting agent showed basophilic, amorphous, and bubbly-extracellular material with prominent hemorrhage, and resection ∼3 months after lifting agent injection showed prominent hyalinized, pink-amorphous ribbons and globules with a foreign body giant cell reaction and fibrosis. The epicenter of the lifting agents was in the submucosa, and the agents were neither refractile nor polarizable. Because of the morphologic overlap with amyloid, 5 cases were stained with Congo Red, and all cases were negative. In conclusion, awareness of the morphology of these new lifting agents is important for accurate diagnosis and to avoid the diagnostic pitfall of amyloid. These lesions can be definitively distinguished from amyloid by their nonreactivity on a Congo Red and familiarity with their characteristic clinicopathologic presentation.